Effects of far ultra-violet radiation and oxygen on macromolecular synthesis and protein induction in Bacteroides fragilis Bf-2 - Schumann, Jacoba Petronella (Department of Molecular and Cell Biology, 2016)
Bibliography: pages 256-363.